Therapy in making handicrafts for patients with mental disorder at the Bani Amrini psychiatric home care - Sri Wahyuningsih; Bani Eka Dartiningsih; Mohammad Hafidori; Muhamad Ali Shodiqin; Monigh Nabilah Amirah Firdaus; Nur Fatika Putri Mei Sari; Agil Putri Mar’atus Sholikhah (Community Empowerment, 2023)
The Bani Amrini is one of the psychiatric home cares in Bangkalan Regency. In its operational activities as a rehabilitation location for patients with mental disorder (ODGJ), this psychiatric home care only uses religious therapy methods (psychoreligious). Even though there are also other methods that can also be used, such as handycraft therapy for ODGJ. The ignorance of the caretakers of the psychiatric home care about handycraft therapy made the Trunojoyo Madura University Community Service Team move to help provide training on making simple handicrafts for ODGJ at the Bani Amrini Mental Institution. The training was carried out with the practical method. This training has proven to be an alternative solution to filling in the free time of ODGJ so that cognitively, affectively and psychomotorically function properly and do not often daydream which causes relapses.